IFNAR signaling in fibroblastic reticular cells can modulate CD8+ memory fate decision. Issue 6 (20th April 2022) - Knop, Laura; Spanier, Julia; Larsen, Pia‐Katharina; Witte, Amelie; Bank, Ute; Dunay, Ildiko R.; Kalinke, Ulrich; Schüler, Thomas
Abstract: CD8 + memory T cells (TM ) are crucial for long‐term protection from infections and cancer. Multiple cell types and cytokines are involved in the regulation of CD8 + T cell responses and subsequent TM formation. Besides their direct antiviral effects, type I interferons (IFN‐I) modulate CD8 + T cell immunity via their action on several immune cell subsets. However, it is largely unclear how nonimmune cells are involved in this multicellular network modulating CD8 + TM formation. Fibroblastic reticular cells (FRCs) form the 3D scaffold of secondary lymphoid organs, express the IFN‐I receptor (IFNAR), and modulate adaptive immune responses. However, it is unclear whether and how early IFNAR signals in lymph node (LN) FRCs affect CD8 + TM differentiation. Using peptide vaccination and viral infection, we studied CD8 + TM differentiation in mice with an FRC‐specific IFNAR deletion (FRC ΔIFNAR ). We show here that the differentiation of CD8 + TCR‐transgenic T cells into central memory cells (TCM ) is enhanced in peptide‐vaccinated FRC ΔIFNAR mice. Conversely, vesicular stomatitis virus infection of FRC ΔIFNAR mice is associated with impaired TCM formation and the accumulation of vesicular stomatitis virus specific double‐positive CD127 hi KLRG‐1 hi effector memory T cells. In summary, we provide evidence for a context‐dependent contribution of FRC‐specific IFNAR signaling to CD8 + TM differentiation. Abstract : Fibroblastic reticular cells (FRCs) modulate CD8 + T cell responses. However, their long‐term impact on the composition of the resulting CD8 + memory T cell (TM ) pool is poorly defined. Using FRC‐specific IFNAR knockout mice (FRC ΔIFNAR ), we provide evidence for the modulation of CD8 + TM differentiation by early IFNAR signals in FRCs.